Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1471-2490-13-45
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mirabegron in patients with and without prior antimuscarinic therapy for overactive bladder: a post hoc analysis of a randomized European-Australian Phase 3 trial

Abstract: BackgroundAntimuscarinic agents are currently the predominant treatment option for the clinical management of the symptoms of overactive bladder (OAB). However, low rates of persistence with these agents highlight the need for novel, effective and better-tolerated oral pharmacological agents. Mirabegron is a β3-adrenoceptor agonist developed for the treatment of OAB, with a mechanism of action distinct from that of antimuscarinics. In a randomized, double-blind, placebo- and active-controlled Phase 3 trial con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 22 publications
(31 reference statements)
1
43
0
Order By: Relevance
“…30 Furthermore, in a post-hoc analysis of the SCORPIO trial, designed to evaluate efficacy in treatment-naïve patients and in those previously treated with an antimuscarinic, mirabegron demonstrated significant reductions in frequency and incontinence in both subgroups, while the response to tolterodine ER 4 mg was similar to placebo. 31 The pooled analysis also demonstrated that the tolerability profile of mirabegron was similar to that of placebo and tolterodine ER 4 mg, with the exception of dry mouth, where the incidence was five times higher with tolterodine ER 4 mg than with mirabegron. 32 In a review of clinical trials of up to 12 months, the most common adverse events (AEs) observed with mirabegron were hypertension, nasopharyngitis, and urinary tract infection.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…30 Furthermore, in a post-hoc analysis of the SCORPIO trial, designed to evaluate efficacy in treatment-naïve patients and in those previously treated with an antimuscarinic, mirabegron demonstrated significant reductions in frequency and incontinence in both subgroups, while the response to tolterodine ER 4 mg was similar to placebo. 31 The pooled analysis also demonstrated that the tolerability profile of mirabegron was similar to that of placebo and tolterodine ER 4 mg, with the exception of dry mouth, where the incidence was five times higher with tolterodine ER 4 mg than with mirabegron. 32 In a review of clinical trials of up to 12 months, the most common adverse events (AEs) observed with mirabegron were hypertension, nasopharyngitis, and urinary tract infection.…”
Section: Introductionmentioning
confidence: 79%
“…The extent to which the results of the current analysis can be extrapolated to treatment-naïve patients is not clear. However, it is notable that in a post-hoc analysis of data from the SCORPIO study, the effect of mirabegron in treatment-naïve patients was greater than that observed with tolterodine ER 4 mg. 31 A number of other antimuscarinic agents are available in Canada for treating OAB (oxybutynin, solifenacin, trospium, and fesoterodine). The cost-effectiveness of mirabegron vs. these agents in Canada is not known.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations